Hemocompatible 3D Silver(I) Coordination Polymers: Synthesis, X‐ray Structure, Photo‐Catalytic and Antibacterial Activity. Issue 18 (14th May 2018) - Kulovi, Somnath; Dalbera, Subrata; Dey, Surya Kanta; Maiti (Choudhury), Sujata; Puschmann, Horst; Zangrando, Ennio; Dalai, Sudipta
Abstract: Three new Ag(I) coordination polymers, namely, [Ag3 (pyp)3 (H2 O)2 ](bpydc)1.5(H2 O)6 (1 ), Ag2 (dpe)2 (phdac)](H2 O)5.4 (2 ), and [Ag2 (azbpy)3 (H2 O)2 ].(dga)(H2 O)5 (3 ) (where pyp=1, 3‐bis(4‐pyridylpropane), H2 bpydc=2, 2'‐bipyridine‐5, 5'‐dicarboxylic acid, dpe=1, 2‐di(4‐pyridyl)ethylene, H2 phdac=1, 4‐phenylenediacetic acid, azpy=4, 4'‐azobispyridine and H2 dga=diglycolic acid) were synthesized and characterized using elemental analysis, IR, UV–vis, fluorescence spectroscopy, and single crystal X‐ray diffraction. The most interesting aspect of these coordination polymers (CPs) in the solid state is represented by the number of lattice water molecules that, along with carboxylate ligands, play a crucial role in network formation through H‐bonds to attain a 3D structure. The band gap energies of the CPs were calculated. Among the compounds studied CP 2 was proved to be the most efficient photocatalyst for the degradation of noxious organic dye methylene blue (MB) and in addition tendered better antibacterial activity. Finally, all three CPs showed to be hemocompatible. Abstract : New photocatalytic silver(I) coordination polymers have been synthesized by usingdiverse N‐ and O‐ donor ligandsand characterized by X‐ray single crystal structural determination. These coordination polymers are hemocompatible and exhibit decent antibacterial property.